CHALLENGES IN CROSS CULTURAL ADVERTISING - Yuni Retnowati (Humaniora, 2015)
At first, marketing practitioners and academics consider standardized approaches to marketing and advertising strategies in globalization, and then some studies proved that the standardization of advertising across culture is not valid. Therefore, cross cultural advertising takes local culture into account when conveying messages in advertisements. Cross cultural understanding is very important in order to produce successful localized advertising that would reflect the cultural values and norms of intended audience. Challenge in cross cultural advertising is the problem of communicating to people of diverse cultural background. Cross cultural solutions are applied in areas such as language, communication style, images and cultural values. Cross cultural advertising is simply about using common sense and analyzing how the different elements of an advertising campaign are impacted by culture and modifying them to best speak to the target audience. Other challenges are determining between standardization and adaptation of cultural values content of advertising when facing different people from diverse cultures. In academic side, the challenge is preparing students to design advertisements that communicate effectively to diverse cultures.